Self-reported Disability in Patients with Inflammatory Bowel Disease Largely Determined by Disease Activity and Illness Perceptions. Issue 2 (February 2015) - van der Have, Mike; Fidder, Herma H.; Leenders, Max; Kaptein, Ad A.; van der Valk, Mirthe E.; van Bodegraven, Ad A.; Dijkstra, Gerard; de Jong, Dirk J.; Pierik, Marieke; Ponsioen, Cyriel Y.; van der Meulen-de Jong, Andrea E.; van der Woude, C. Janneke; et al.
Abstract : Background: The inflammatory bowel disease (IBD) disability index has recently been introduced to measure patients' physical, psychological, familial, and social limitations associated with IBD. We assessed factors related to self-reported disability and the relationship between disability and direct health care costs. Methods: A large cohort of patients with Crohn's disease (CD) and ulcerative colitis (UC) was prospectively followed for 2 years by 3 monthly web-based questionnaires. At 2 years, patients completed the IBD disability index, with lower score indicating more disability. Linear regression analysis was used to examine the impact of demographics, clinical characteristics, and illness perceptions on self-reported disability. Trends in direct health care costs across the disability severity groups minimal, mild, moderate, and severe, were tested. Results: A total of 554 patients with CD and 424 patients with UC completed the IBD disability index (response rate, 45%). Both clinical characteristics and illness perceptions significantly contributed to self-reported disability (45%–47%, P = 0.000 and 8%–12%, P = 0.000, respectively). Patients with CD scored lower on the self-reported IBD disability index than patients with UC (0.255 versus 3.890, P < 0.000), indicating more disability in patients with CD. Factors independently associated with higher self-reported disability rates were increased disease activity, illness identity (higher number of symptoms attributed to IBD), and stronger emotional response. Disease duration and disease phenotype were not associated with self-reported disability. Direct health care costs increased with the worsening of self-reported disability ( P = 0.000). Conclusions: More disability was reported by patients with CD than by UC. Self-reported disability in IBD was mainly determined by clinical disease activity and illness perceptions but not by disease duration or disease phenotype. Abstract : Article first published online 7 January 2015.Supplemental Digital Content is Available in the Text.